Genetic Diversity and Population Structure of a Threatened African Tree Species, Milicia excelsa, Using Nuclear Microsatellites DNA Markers - Christine Ouinsavi; Nestor Sokpon; Damase P. Khasa (International Journal of Forestry Research)
To accurately estimate the genetic diversity and population structure for improved conservation planning of Milicia excelsa tree, 212 individuals from twelve population samples covering the species' range in Benin were surveyed at seven specific microsatellite DNA loci. All loci were variable, with the mean number of alleles per locus ranging from 5.86 to 7.69. Considerable genetic variability was detected for all populations at the seven loci (AR=4.60; HE=0.811). Moderate but statistically significant genetic differentiation was found among populations considering both FST (0.112) and RST (0.342). All of the populations showed heterozygosity deficits in test of Hardy-Weinberg Equilibrium and significantly positive FIS values due to inbreeding occurring in the species. Pairwise FST values were positively and significantly correlated with geographical distances (r=0.432; P=.007, Mantel's test) indicating that populations are differentiated by “isolation by distance.” Bayesian analysis of population structure showed division of the genetic variation into four clusters revealing the existence of heterogeneity in population genetic structure. Altogether, these results indicate that genetic variation in Milicia excelsa is geographically structured. Information gained from this study also emphasized the need for in situ conservation of the relict populations and establishment of gene flow corridors through agroforestry systems for interconnecting these remnant populations.